2004
DOI: 10.1097/01.mlg.0000149457.13877.d5
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Glossopharyngeal Nerve Paralysis after Tonsillectomy: Case Report and Anatomic Study

Abstract: Direct nerve injury seems the most plausible explanation for this rare complication of tonsillectomy. The proximity of the glossopharyngeal nerve to the tonsillar fossa emphasizes the importance of maintaining the correct surgical plane during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Identification and preservation of the glossopharyngeal nerve, which provides sensation to the tongue and pharynx, as well as motor function to the stylopharyngeus muscle and some of the superior constrictor, 2,3 may help decrease the morbidity of dysphagia after transoral tumor resection. [6][7][8] Injury to this nerve may also have implications for the development of dysgeusia. 9 Possible indirect damage to the glossopharyngeal nerve or its lingual branch is suspected as a possible cause of the taste disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification and preservation of the glossopharyngeal nerve, which provides sensation to the tongue and pharynx, as well as motor function to the stylopharyngeus muscle and some of the superior constrictor, 2,3 may help decrease the morbidity of dysphagia after transoral tumor resection. [6][7][8] Injury to this nerve may also have implications for the development of dysgeusia. 9 Possible indirect damage to the glossopharyngeal nerve or its lingual branch is suspected as a possible cause of the taste disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the lingual branch of the glossopharyngeal nerve provides sensation to the posterior tongue and enters the tongue base by traveling through the constrictor muscles in the area of the glossotonsillar sulcus . It has been suggested that injury to this nerve branch may contribute to dysphagia and dysgeusia after palatine or lingual tonsillectomy . An improved understanding of the anatomy of the glossopharyngeal nerve may help to prevent inadvertent injury to this nerve during oropharyngeal surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taste disorders following TE were reported as case reports [273], [274], [275], [276], [277], [278], [279], [280], [281], [282], [283], [284], [285], [286], [287], [288], [289], [290], [291], [292] or subject of studies [234], [293], [294], [295], [296], [297], [298], [299], [300], [301], [302], [303], [304], [305], [306]. Depending on the population size studied and follow-up the rate varies between 0% [293] and 25.7% [234].…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, the phenomenon is transient [304]. Taste disorders may be accompanied by dysphagia [275], [280], [281], [282], [285], [287], hypesthesia [234], [273], [276], [278], [285], [289] or pain [234], [286], [289], [295]. Bicknell [277], Tomita [300] and Tomofuji [294] used oral zinc therapy to treat dysgeusia which has been successful in another patient even several years after surgery [308].…”
Section: Discussionmentioning
confidence: 99%